2015
DOI: 10.1039/c5sm00530b
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous flow kinematics of cellulose nanofibril suspensions under shear

Abstract: The rheology of NFC suspensions that exhibited different microstructures and colloidal stability, namely TEMPO and enzymatic NFC suspensions, was investigated at the macro and mesoscales using a transparent Couette rheometer combined with optical observations and ultrasonic speckle velocimetry (USV). Both NFC suspensions showed a complex rheology, which was typical of yield stress, non-linear and thixotropic fluids. Hysteresis loops and erratic evolutions of the macroscale shear stress were also observed, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 56 publications
(95 reference statements)
2
65
0
Order By: Relevance
“…Copyright 2004 EDP Sciences), which allows recording of (e) velocity maps (adapted from ref. 33 . Copyright 2015, with permission of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23…”
Section: Local Flow Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Copyright 2004 EDP Sciences), which allows recording of (e) velocity maps (adapted from ref. 33 . Copyright 2015, with permission of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23…”
Section: Local Flow Propertiesmentioning
confidence: 95%
“…In addition to the visual observation of the CNF structure discussed above, Martoïa et al 33 compared the rheological behavior of enzymatically hydrolyzed and TEMPO-oxidized CNF suspensions using Couette geometry combined with USV. In their work, it was shown that for both types of CNF suspensions the flow was affected by the presence of wall-slip and multiple flow bands, which evolved with applied shear rate.…”
Section: Local Flow Propertiesmentioning
confidence: 99%
“…Floculation, fiber entanglement and wall slippage are phenomena present in this system due to the particles characteristics, i.e. size polidispersity, flexibility and surface charge [26,29] . …”
Section: Flow Curvesmentioning
confidence: 99%
“…In this case the torque, rather than the pressure drop, is used to quantify viscous losses. Ultrasound speckle velocimetry was used to characterise fatigue due to shear in gels (Gibaud et al 2016), flow banding in cellulose nanofibril suspensions (Martoïa et al 2015), flow instabilities and shear banding in a non-Newtonian micellar solution (Gallot et al 2013) and avalanche-like fluidisation events in suspensions (Kurokawa et al 2015). Again, most of these systems are inherently echogenic and do thus not require seeding.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%